SOLAR PROTECTION ESTHETICISTS, PHYSICAL EDUCATORS AND PHYSICALLY ACTIVE (Fiep Bulletin - online, 2014)
The regular practice of physical activity is an important action for the promotion of health, beauty and wellness . And when combined with a balanced diet and controlling stress levels , it then promotes quality of life . But, practitioners of routine physical activity , in many cases , are exposed to the sun, which causes damage , early and late , to the skin . Examples of injury : burns , photoalergies, premature aging , immunosuppression and the worst of them , skin cancer. The Environmental Protection Agency , based on progressive reduction of ozone, reports that from 1991 to 2030 will be diagnosed approximately 12 million new cases of Non Melanoma Skin Cancer , leading to over 200,000 deaths . ( CUCÉ and NETO , 2001) The adequate photoprotection can prevent these deleterious effects , but it is not adopted by the community practitioner of physical activity and not by the general population . Consciousness begins only in old age when the first signs of excessive sun appear on the skin : blemishes , wrinkles , pre-cancerous lesions , such as actinic keratosis .
Keywords: Sunscreen; Photoprotection; Skin Cancer .